ANALISIS ANTUSIASME SISWA DALAM EVALUASI BELAJAR MENGGUNAKAN PLATFORM QUIZIZZ - Lailatul Asria; Dwi Ratna Sari; Siti Anifatul Ngaini; Umi Muyasaroh; Fadhilah Rahmawati (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2021)
One way to evaluate student learning outcomes is through question processing. However, nowadays evaluations are usually carried out using conventional methods such as a paper-based test. Even though often in the implementation of evaluations, students feel less enthusiastic about their work. This study aims to identify students' enthusiasm in solving questions through the Quizizz platform. The subjects of this study were 34 students of class XI Science 4 Senior High School 1 Tahunan. This research uses a descriptive quantitative method because shows a description of the students' enthusiasm for using the Quizizz platform as a tool for solving trigonometric questions. To analyze the enthusiasm of students in solving questions through the Quizizz platform, was carried out in three stages: 1) distributing a questionnaire with 25 question items via Google Form based on five indicators that measure enthusiasm (Response, attention, concentration, willingness, and self-involvement), 2) questionnaire data analyzed based on the answer score for each question item. Based on the research results, student enthusiasm in learning evaluation on trigonometric material through the Quizizz platform got a percentage of 62.38%. So that the Quizizz platform can be an alternative for teachers in evaluating student learning outcomes to create an atmosphere of evaluation that is fun and interesting for students to follow which will increase student enthusiasm in participating in learning evaluations.